From the microscopic interaction mechanism to the grinding temperature field: An integrated modelling on the grinding process. (November 2016) - Jiang, Jingliang; Ge, Peiqi; Sun, Shufeng; Wang, Dexiang; Wang, Yuling; Yang, Yong
Abstract: The microscopic interaction mechanism between grains and workpiece material in grinding contact zone is extremely complicated which will take many interrelated and coupled factors into consideration, such as grinding wheel topographies, grain distributions, physical and mechanical properties of material, the emergence of grinding forces and heat energies, the partitioning and transfer of grinding heat, etc. However, the current theories and models are unable to integrate all of the above factors into an organic-whole model. Former researchers usually focused on several of above aspects and made assumptions to simplify those theories. However, these assumptions will weaken the mathematical relationship between grinding conditions and ground surface qualities and will increase the difficulties of understanding on the nature of grinding process. The work of this paper is an attempt on this purpose. It is based on the author's previous work of a microscopic interaction mechanism model between grains and workpiece material in grinding contact zone which will describe the interaction situation of a grain with any size, protrusion height and location, then the distributions of each type of grains were obtained. Single plowing and cutting grain force models were developed based on R.L. Hecker's single grain force model and M.E. Merchant's metal cutting theory, then led into grinding force distribution. The heat partition ratio model of W.B. Rowe was applied on the discrete grinding contact zone, a new developed heat flux profile transferred into workpiece surface was obtained, which was usually assumed to be rectangular, triangular and parabolic in shape in former researches. In order to confirm the rationality of this new heat flux profile, a comparison on temperature fields and grinding forces has been made between results from FE-models and experiments, under both wet and dry grinding conditions. Comparison results showed that this new developed integrated grinding process model has more precise prediction ability on grinding forces and grinding temperatures. Highlights: A new model on the grinding process was developed for predicting grinding force, heat flux, heat partition radio and temperature field precisely. The new deduced heat flux into workpiece surface is more like a quadratic curve, and has more precise predicting ability than traditional models. The model developed in this work was validated by experiments on grinding forces and temperatures under both wet and dry grinding conditions.